Modern Fluvio-Lacustrine System of Lake Singkarak, West Sumatra and Its Application as An Analogue for Upper Red Bed Fm. in the Central Sumatra Basin - Enry Horas Sihombing; Nadya Oetary; Iqbal Fardiansyah; Reybi Waren; Endo Finaldhi; Faizil Fitris; Habash Semimbar; Satia Graha; Abdullah F. Talib; Willy R. Paksi (Ikatan Ahli Geologi Indonesia, 2016)
Paleogene synrift fluvio-lacustrine rocks in western Indonesian basins are viable and prolific petroleum plays. However, due to active tectonics and confined environment, reservoir distribution and geometry of these Paleogene rocks are highly complex. In order to better understand and identify stratigraphic relationships and facies geometries in Paleogene synrift reservoirs, a field study on analogous modern alluvial-fan and axial-fluvial deltas in Lake Singkarak has been performed by investigating data from various elements of the depositional system. The results of this study illustrate how an integration of grain texture, faunal analysis, depositional facies, and stratigraphic stacking patterns in a modern depositional environment can characterize the complexity of reservoir geometry, reservoir quality and their distribution, both laterally and vertically.This study focuses on modern sediment of Sumpur axial-fluvial delta and Malalo alluvial fan delta in the northern part of Lake Singkarak, West Sumatra Province. Seven depositional facies were recognized in the Sumpur axial-fluvial delta including fluvial, upper and lower distributary channel, subaqueous distributary channel, mouth bar, shoreline, and abandoned delta. From a sand quality and facies geometry perspective, the lower distributary channel, subaqueous distributary channel and mouth bar facies are associated with the most favourable reservoir potential. The Malalo alluvial-fan delta can be subdivided into four depositional facies including upper, middle, lower, and subaqueous fan facies. The highest reservoir quality exists in the lower and subaqueous fan facies. These two deltaic systems exhibit that the highest quality reservoirs occur in the more distal setting and their distribution in the axial-fluvial delta is more regionally extensive than it is in the alluvial fan delta.The model from Lake Singkarak was then compared to Paleogene reservoirs in “NAT” Field, Central Sumatra Basin. The field produced hydrocarbons from synrift deposits within Upper Pematang Group. The comparison was done with an objective to use Lake Singkarak as the analog depositional model for the Upper Pematang Group.